Features of interrogation in the investigation of economic crimes committed by corrupt officials (Journal of actual problems of jurisprudence, 2019)
The article is devoted to the study of the peculiarities of interrogation of officials, carried out in the investigation of economic crimes. The article deals with issues related to the determination of the objectives of the interrogation of officials involved in the commission of an economic crime; the classification of persons to be interrogated; establishing the circumstances affecting the giving of incomplete and biased data; the study of typical situations that arise when interrogating suspects (accused) in conflict conditions; the study of methods of identifying and exposing false testimony, etc. On the basis of the study conducted, the features of interrogation during the investigation of economic crimes are summarized. Recommendations on the effective use of interrogation are formulated, including when preparing for the interrogation of suspects (accused) in cases of this category, including the study of the necessary documents, regulatory sources, special literature, opinions of experts, and other collected evidence regarding the purpose of interrogation; timely seizure and inspection of the necessary documents, the formation of a testimony base, the conduct of relevant research, including examinations, the data of which can confirm or deny the testimony of the interrogated persons; obtaining the necessary information about the person being questioned, his intellectual, business qualities, knowledge and experience, characteristic features, psychological state, attitude to the investigation, etc., the source of which may be witness testimony, ORD materials, official reference information, etc .; selection of relevant documents, protocols of other investigative actions, regulatory material that may be needed during interrogation; gathering evidence that refutes possible statements by the interviewees that they are negotiated, or that the investigator’s statements “do not have anything to do with themselves”; drawing up a written interrogation plan (this is especially important for beginning investigators), which should not be a rigid algorithm for certain questions, but an extensive perspective of the dialogue depending on the possible course of conduct of the person being questioned, the nature of the new information that the latter reports. The scientific and methodological basis was made by the laws of the Republic of Kazakhstan, the Criminal Code of the Republic of Kazakhstan, the Criminal Procedure Code of the Republic of Kazakhstan, as well as the works of well-known forensic scientists of Kazakhstan and foreign countries. Key words: Interrogation, investigative actions, investigation, prosecution, specificity of interrogation, tactical task, investigator, suspect, accused, crime, corruption.